2012
DOI: 10.1063/1.3686538
|View full text |Cite
|
Sign up to set email alerts
|

Theory and simulation of 1D TO 3D plastic relaxation in tantalum

Abstract: (2003)Abstract. In plane shockwaves the uniaxial strain rate can greatly exceed the rate at which dislocation flow can relax the concomitant shear stress. The result is an overdriven plastic state in which the compression is 1D uniaxial initially and only after a period of time does the lattice relax to a more 3D compressed state due to plastic flow. Here we use an analytic calculation based on a generalization of the Gilman model of flow involving dislocation evolution to predict the phases of plastic relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 13 publications
3
19
1
Order By: Relevance
“…Utilizing molecular dynamics (MD) simulations, Rudd et al showed that in Ta, homogenous nucleation is expected to occur at normal stresses above 62 GPa under laser driven conditions, which is a higher normal stress and strain rate than observed in these experiments 28 .…”
Section: A Dislocation Densitymentioning
confidence: 99%
“…Utilizing molecular dynamics (MD) simulations, Rudd et al showed that in Ta, homogenous nucleation is expected to occur at normal stresses above 62 GPa under laser driven conditions, which is a higher normal stress and strain rate than observed in these experiments 28 .…”
Section: A Dislocation Densitymentioning
confidence: 99%
“…Shock-induced plasticity in tantalum, a body-centered cubic metal, has been studied extensively, with post facto analyses [6,[16][17][18][19] being complemented by a number of MD studies [9,[20][21][22][23]. Here we use XRD to directly monitor lattice orientations during shock release.…”
mentioning
confidence: 99%
“…Coordinate system for analysis of the diffraction images from a polycrystalline vanadium sample situated as shown in the x, y plane at the base of the pyramidal BBXRD x-ray diffraction camera. The ray path from the collimated x-ray source lies in the x, z plane and is incident at 45 at the surface of the sample. Debye-Scherrer diffraction from (002) planes of vanadium is shown schematically on the bottom (negative-y side) image platecompare Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In this way, Debye-Scherrer diffraction images from both the undisturbed material ahead of the shock and the shock-compressed vanadium are recorded simultaneously. The 45 angle of incidence of the x-ray probe beam relative to the direction of propagation of the shock was chosen to provide sensitivity in the diffraction images to anisotropic strain of the shock-compressed vanadium.…”
Section: Methodsmentioning
confidence: 99%